Identification of Dietary Phytochemicals Capable of Enhancing the Autophagy Flux in HeLa and Caco-2 Human Cell Lines - Kohta Ohnishi; Satoshi Yano; Moe Fujimoto; Maiko Sakai; Erika Harumoto; Airi Furuichi; Masashi Masuda; Hirokazu Ohminami; Hisami Yamanaka-Okumura; Taichi Hara; Yutaka Taketani (MDPI AG, 2020)
Autophagy is a major degradation system for intracellular macromolecules. Its decline with age or obesity is related to the onset and development of various intractable diseases. Although dietary phytochemicals are expected to enhance autophagy for preventive medicine, few studies have addressed their effects on the autophagy flux, which is the focus of the current study. Herein, 67 dietary phytochemicals were screened using a green fluorescent protein (GFP)-microtubule-associated protein light chain 3 (LC3)-red fluorescent protein (RFP)-LC3ΔG probe for the quantitative assessment of autophagic degradation. Among them, isorhamnetin, chrysoeriol, 2,2',4'-trihydroxychalcone, and zerumbone enhanced the autophagy flux in HeLa cells. Meanwhile, analysis of the structure-activity relationships indicated that the 3'-methoxy-4'-hydroxy group on the B-ring in the flavone skeleton and an ortho-phenolic group on the chalcone B-ring were crucial for phytochemicals activities. These active compounds were also effective in colon carcinoma Caco-2 cells, and some of them increased the expression of p62 protein, a typical substrate of autophagic proteolysis, indicating that phytochemicals impact p62 levels in autophagy-dependent and/or -independent manners. In addition, these compounds were characterized by distinct modes of action. While isorhamnetin and chrysoeriol enhanced autophagy in an mTOR signaling-dependent manner, the actions of 2,2',4'-trihydroxychalcone and zerumbone were independent of mTOR signaling. Hence, these dietary phytochemicals may prove effective as potential preventive or therapeutic strategies for lifestyle-related diseases.